Singlet and triplet trions in WS2 monolayer encapsulated in hexagonal boron nitride. (7th June 2018) - Vaclavkova, D; Wyzula, J; Nogajewski, K; Bartos, M; Slobodeniuk, A O; Faugeras, C; Potemski, M; Molas, M R
Abstract: Embedding a WS2 monolayer in flakes of hexagonal boron nitride allowed us to resolve and study the photoluminescence response due to both singlet and triplet states of negatively charged excitons (trions) in this atomically thin semiconductor. The energy separation between the singlet and triplet states has been found to be relatively small reflecting rather weak effects of the electron–electron exchange interaction for the trion triplet in a WS2 monolayer, which involves two electrons with the same spin but from different valleys. Polarization-resolved experiments demonstrate that the helicity of the excitation light is better preserved in the emission spectrum of the triplet trion than in that of the singlet trion. Finally, the singlet (intravalley) trions are found to be observable even at ambient conditions whereas the emission due to the triplet (intervalley) trions is only efficient at low temperatures.